A 3D gene expression atlas of the floral meristem based on spatial reconstruction of single nucleus RNA sequencing data - Neumann, Manuel; Xu, Xiaocai; Smaczniak, Cezary; Schumacher, Julia; Yan, Wenhao; Blüthgen, Nils; Greb, Thomas; Jönsson, Henrik; Traas, Jan; Kaufmann, Kerstin; Muino, Jose M. (Nature Communications, 2022)
Cellular heterogeneity in growth and differentiation results in organ patterning. Single-cell transcriptomics allows characterization of gene expression heterogeneity in developing organs at unprecedented resolution. However, the original physical location of the cell is lost during this methodology. To recover the original location of cells in the developing organ is essential to link gene activity with cellular identity and function in plants. Here, we propose a method to reconstruct genome-wide gene expression patterns of individual cells in a 3D flower meristem by combining single-nuclei RNA-seq with microcopy-based 3D spatial reconstruction. By this, gene expression differences among meristematic domains giving rise to different tissue and organ types can be determined. As a proof of principle, the method is used to trace the initiation of vascular identity within the floral meristem. Our work demonstrates the power of spatially reconstructed single cell transcriptome atlases to understand plant morphogenesis. The floral meristem 3D gene expression atlas can be accessed at http://threed-flower-meristem.herokuapp.com.
Gesehen am 28.06.2022